Epidemiology of Neonatal Cancer and its Correlation with Different Factors - Maliheh Kadivar; mahsa asadabadi (Mashhad University of Medical Sciences, 2017)
Background: Tumors are among the main causes of neonatal intensive care unit (NICU) admission. We aimed to determine the frequency distributions and presentations of tumors in newborns admitted to the NICU of a children's medical center. Methods: In this observational cross-sectional study, we reviewed medical records of 53 neonates admitted to the NICU of a children's medical center during 2004-2015. The demographic characteristics, maternal history, ultrasound findings during pregnancy, and family history of cancer were considered along with clinical presentations. To determine the tumor type, imaging and pathological reports were collected from the medical records. Tumors were classified according to the International Classification for Childhood Cancer criteria (ICCC). The gathered data were analyzed using SPSS, version 19. Results: The mean maternal age and gestational age of the newborns were 24.4±4.9 years and 37.4±2.01 weeks, respectively. Twenty-nine (54.7%) subjects were female, and 12 (22.6%) infants were preterm. The parents of 19 infants (35.8%) had consunguity, but positive family history was not identified in any of the newborns. Thirteen (24.5%) patients had congenital anomalies. Neonatal cancer was diagnosed through prenatal ultrasonography in 16 (30.2%) infants, and 17 (32%) cases had malignant tumors. Among these newborns, 37 (69.8%) underwent surgery, 13 (24.5%) patients received medications, 1 (1.9%) patient had chemotherapy, and 2 (3.8%) patients received both surgery and chemotherapy. Ten (18.9%) subjects died at the end of the study. Furthermore, 18 (34%) tumors were mature teratomas, 11 (20.8%) cases were hemangiomas, 7 (13.2%) were neuroblastomas, and 6 (11.3%) cases were lymphangiomas. Conclusion: According to the results of this study, teratoma is the most common tumor among the newborns admitted to NICUs, and head and neck were the most common locations. In addition, neuroblastoma was associated with the highest mortality rate in this study.